Fitness profiling in handball: Physical and physiological characteristics of elite players - Sporis, G.; Vuleta, D.; Vuleta Jr., D.; Milanovic, D. (Collegium Antropologicum, 2010)
The purpose of this study was to describe the structural and functional characteristics of elite Croatian handball players and to evaluate whether the players in different positional roles have different physical and physiological profiles. According to the positional roles, players were categorized as goalkeepers (n=13), wing players (n=26), backcourt players (n=28) and pivot players (n=25). The goalkeepers were older (p<0.01), and the pivot players were more experienced (p<0.01) than the backcourt players. The wings were the shortest players in the team. The pivots were tallest and heavier than the backcourt and wing players (p<0.01), whereas the backcourt players were tallest then wings (p<0.01). Goalkeepers had more body fat than the backcourt and wing players (p<0.01). The backcourt players had a lower percentage of body fat. The backcourt players were the quickest players in the team when looking at values of maximal running speed on a treadmill. The Goalkeepers were the slowest players in the team (p<0.01). The best average results concerning maximal heart rate were detected among the backcourt players. There were no statistically significant differences between the players` positions when measuring blood lactate and maximal heart rate. A strong negative correlation was found between body fat and maximal running speed (r=-0.68, p<0.01). Coaches are able to use this information to determine which type of profile is needed for a specific position. Experienced coaches can used this information in the process of designing a training program to maximize the fitness development of handball players, with one purpose only, to achieve success in handball.